Older people receiving family‐based support in the community: a survey of quality of life among users of 'Shared Lives' in England. (29th January 2017) - Callaghan, Lisa; Brookes, Nadia; Palmer, Sinead
Abstract: Shared Lives (adult placement) is a model of community‐based support where an adult who needs support and/or accommodation moves into or regularly visits the home of an approved Shared Lives carer, after they have been matched for compatibility. It is an established but small service which has been used mainly by people with learning disabilities but which has the potential to offer an alternative to traditional services for some older people. However, there is little research on the outcomes for older users of Shared Lives. This paper presents findings from a survey of 150 older people using Shared Lives support across 10 Shared Lives schemes in England, which took place between June 2013 and January 2014. The aim was to identify outcomes for older users of Shared Lives and compare these to outcomes for older users of other social care services. In the absence of an ideal study design involving randomised allocation, statistical matching was used to generate a comparison group from the Adult Social Care Survey from 2011/12, with 121 cases matched to 121 Shared Lives cases. The main outcome measures were Social Care‐Related Quality of Life (measured by the ASCOT) and overall quality of life. Findings indicated that Shared Lives can deliver good outcomes for older people, particularly for overall quality of life. In comparison to the matched group of older people using other forms of support, there was some evidence that Shared Lives may deliver better outcomes in some aspects of quality of life. Limitations to the research mean, however, that more work is needed to fully understand the role Shared Lives could play in supporting older people.